ANALISIS PENGENDALIAN KUALITAS PRODUKSI DOOR LOCK DENGAN METODE PDCA BERDASARKAN SISTEM KAIZEN DI PT.X - Syahriza, Dini; Zaky, Muhammad; Suherlan, Suherlan (Program Studi Teknik Industri, Fakultas Teknik. Universitas Samudra, 2022)
X is a company engaged in the manufacture of automotive components that produce car parts. Market PT. X is not only to local only, but to the majority of international magnitude. In the process of production of the door lock (konci car door) are found reject the results because the process is less rigorous and order goods (parts) of the subcontracts that are not in accordance with the SOP process. Among them there are sizes that do not fit and less tidy. So there is a complaint from the central hub Door Lock resulting difficulty in mounting Door Lock. The research objective is to improve a system on quality control in the production process of door lock with PDCA method based on system KAIZEN, because there are irregularities in the production process resulting Door Lock missing goods, resulting in complaints from the central hub Door Lock. From the data processing period January 2019 s / d in May 2019 from Table 4.1 above shows a decrease of 45 the amount of damage that occurred engine resulting in decreased also against defective products against total disability of 99.83% and the overall probability of 13.33% when compared with the period January 2018 s / d December 2018 amounted to 10.13% and the probability of 16.14% it means that the application of PDCA method using KAIZEN SYSTEM is effective in overcoming the problem of engine damage resulting production defective products miss. Where the results of the application of this method is very profitable company